ANALISIS KESALAHAN SISWA KELAS VII DALAM MENYELESAIKAN SOAL OPERASI BENTUK ALJABAR BERDASARKAN TEORI NOLTING - Arie Rahman Shadiqin; Tina Rosyana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The result of the study show that student still have difficulties in understanding the algebraic operation materials, so students made mistakes in doing evaluation tests.  The Research aims to analyze VII grade students’ mistakes in solving algebraic operations according to Nolting’s Theory. The method used in this research is by using the descriptive qualitative method with the research subject VII grade students in MTs Al-Firdaus Cipatat. The data collection was carried out by giving four questions written test. Then, the datas obtained was processed using the Microsoft Excel. Based on the results of the research that has been obtained from students’ answers, the students carried out the error in interpreting the questions, errors in writing the known and questioned components, the careless error when taking the tasks, errors on do not understand the concepts which were be required to answering the question, error on answering the question with no perfect, and the error on leaving the answer as blank.